Kedudukan Badan Hukum sebagai Subjek Hukum dalam Hukum Ekonomi Syariah - Panji Adam (Syiar Hukum, 2019)
In the study of Islamic economic law the discussion of the contract occupies a very important position. The contract is said to be legally valid when compliance with the terms and conditions for the validity of the sharia agreement. One of the pillars that must be fulfilled is the parties who carry out the contract. In the classical muamalah fiqh study the parties that are the subject of law are only individuals, but as time goes by, there is a development, not only individuals who are legal subjects, but legal entities are subject to law. The position of this legal subject is recognized in the perspective of sharia economic law because it is the result of an analogy of human existence as a legal subject as long as it does not contradict sharia principles. In terms of fiqh muamalah the legal entity is usually called syakhsyiyyah i’tibariyah. The implementation in the context of Islamic economic law is in the form of contemporary partnership agreements.